Perspective and the Blind rappresentazione e comunicazione inclusiva per l'accessibilità dei dipinti prospettici - Ansaldi, Barbara (Beyond accessibility. Cultural Heritage for All, 2023)
Two exploring hands, two eyes that can only imagine. If there is something truly universal in this world, that everyone should be granted access to, that is art in all its forms. Yet, the accessibility of art to people with visual impairment has been for a long time mostly intended as the elimination of architectural barriers; however, it is necessary to work on the sensory, experiential and cognitive aspects, in order to allow blind people to truly access and enjoy artworks, paving the way to the right - for everyone - to live the aesthetic experience. In an inclusive perspective, the book proposes a methodological-didactic approach for all for the 'translation' of perspective-based paintings into a language which can be accessed by visually impaired users. Communicating such works to a non-sighted audience does not only mean to render them into a tactically explorable three-dimensional form: Renaissance perspective-based paintings embody different values, symbolic messages and meanings which are strictly linked to the application of perspective and whose acknowledgment does not pass through the eyes but through understanding and intellect. The proposed methodological approach works on two fronts: firstly, the search for the figurative equivalent of perspective space; secondly, the research on the aesthetic equivalent, which includes the former and completes it, allowing access to the actual aesthetic experience. Therefore, an augmented and inclusive communication of the artwork must include a well-structured didactic apparatus in order to convey not only the visual qualities of the work translated into tactile form but also all the meanings connected to it, including the possible multisensory stimuli it can evoke. Such kind of representational and communication strategies are beneficial to a generic audience as well, providing the opportunity to experience an alternative way to 'enter' the work of art. In particular, the multisensory experience fully reflects the most authentic spirit of inclusion as it adds 'feeling' to the artistic experience, so that sighted people find out they can 'see more', and better. Research methodology is based on the traditional methods of descriptive geometry (reverse perspective, accelerated solid perspective) and Information and Communication Technologies (3D modeling, 3D printing) and it was applied to two case studies, The Feast of Herod in the versions by Benozzo Gozzoli and Filippo Lippi.